2017
DOI: 10.3945/ajcn.116.150540
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-vigorous physical activity, but not sedentary time, predicts changes in cardiometabolic risk factors in 10-y-old children: the Active Smarter Kids Study,

Abstract: Cross-sectional data have suggested an inverse relation between physical activity and cardiometabolic risk factors that is independent of sedentary time. However, little is known about which subcomponent of physical activity may predict cardiometabolic risk factors in youths. We examined the independent prospective associations between objectively measured sedentary time and subcomponents of physical activity with individual and clustered cardiometabolic risk factors in healthy children aged 10 y. We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
56
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 33 publications
14
56
4
1
Order By: Relevance
“…Stamatakis et al . observed an inverse association between MVPA and SBP but that association was attenuated by adjustment of important covariates and baseline value of SBP, which corresponded with the four other studies reporting no prospective associations . However, some studies observed inverse associations in boys; Carson et al .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Stamatakis et al . observed an inverse association between MVPA and SBP but that association was attenuated by adjustment of important covariates and baseline value of SBP, which corresponded with the four other studies reporting no prospective associations . However, some studies observed inverse associations in boys; Carson et al .…”
Section: Resultssupporting
confidence: 79%
“…Sedentary time was unrelated to clustered cardiometabolic risk in prospective studies , even when accounting for MVPA, sleep and adiposity . In contrast, one study observed an unexpected beneficial association between sedentary time and clustered cardiometabolic risk, independent of MVPA .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…These finds are consistent with results of previous studies [7][8][9][10][11][12]18 and reinforce that physical activity is associated to better profile of cardiovascular risk factors independently of sedentary time. Different from the others studies that mostly used accelerometers to estimate physical activity, in the present study pedometers were used.…”
Section: Discussionsupporting
confidence: 93%
“…Although some studies indicate independent associations of the time in physical activities (inverse) and in sedentary time Screen time, physical activity and cardiovascular risk factors in adolescents (direct) with health outcomes [3][4][5][6] , not all results are consistent. Some studies found independent association with health outcomes only to physical activity [7][8][9][10][11][12] and others only to sedentary time [13][14][15] . Most studies reported independent association or effect between one of the behavior and morbidity condition, just adjusting the analyses by the other behavior.…”
Section: Introductionmentioning
confidence: 99%